Symposium 12: A Distributed Multicultural Network for Teaching Information Society: Cultural Diversity Aspects - Siakas, Kerstin V. (Proceedings of the International Conference on Networked Learning, 2008)
In today’s rapidly changing global environment, governments, organisations and citizens face more challenges than ever. Developments in ICTs, the globalisation, as well as the Lisbon and Bologna objectives have set new demands on education, requiring a new paradigm of educational systems and pedagogic processes. As a result, learning is globally susceptible to remarkable changes. Visions and goals of life-long learning have to be defined in order to design the new paradigm of education. The pedagogic process involves a huge complexity comprising internal and external stakeholders, such as students, educators, managers, funding providers and the society as a whole. The product of this complex process is both tangible in the form of qualified learners/graduates and less amendable to quantification in the form of accomplishment of higher level ideals and attitudes as well as transferable knowledge and skills. In order to respond to the changes in technology and the subsequent consequences, proactive policies are needed at European, national and educational institution levels. This paper reports on the experiences gathered from the Network for Teaching the Information Society (NETIS), aiming to meet the emerging requirements by developing a life-long networked technology-based teaching-and-learning environment, by partners from Hungary, England, Estonia, Greece and Slovakia. In particular we discuss challenges of networking in an intercultural diverse environment, including challenges regarding research and teaching Information Society aspects on the same e-learning platform to students from different educational environments, encompassing different disciplines, and from different national cultures with different languages. The importance of taking the cultural particularities and the national ICT environment into consideration is highlighted. Many consider that the internet creates so called "converge values" and that managing and operating ICT in a global context is largely the same as managing and operating ICT in a domestic localized context. The other view proposes that there are differences depending on cultural aspects, different business and legal environments, different languages and varying technology availability. A major critique on the current EU policy process has been articulated regarding the failure of the EU to recognize and adjust its policy to the existing cultural particularities of its Member States. The question seems to be whether digital divides constitute ’cultural divides’ having an impact on the policy, regulation and future evolution of the EU Information Society. The EU policy needs to take into account the socio-cultural particularities of each EU Member State without loosing its broad scope and common aim across the EU. Educational institutions, educators and education procedures influence the pedagogic process, the learning context, as well as the broader societal context comprising political, economic, technological and socio-cultural aspects. On the other hand, the societal context influences institutions within respect to their structures, strategies, management processes and means of operating procedures, including technology and individuals, as well as the context of learning. To address the multicultural diversity, we emphasize particular caution and awareness of particularities, such as differences in national Information Society adoption levels, institutional regulations, disciplines (students from informatics and social sciences), language, attitudes and values, as well as operational issues, such as numbers of students that will participate in the Information Society course in the different countries. Our approach aims to combine classroom experience and research evidence aiming for continuous improvement. The NETIS course is taught for two semesters by using different degrees of blended learning depending on country. In addition to the communication via the Moodle e-learning platform social networks are used for generating content by users (educators and students) and for knowledge sharing. Experiences, both from students and from educators, are evaluated and reported.